Power imbalances in tropical medicine journals: an analysis of editorial board representation - Sushree Nibedita Panda; Manish Barik; P. Ratna; Prabhu Kalyan Das (Tropical Medicine and Health)
Abstract Background Shaped by its colonial origins, tropical medicine sustains inequitable power dynamics in global health, sidelining low-middle-income countries (LMICs) in critical decision-making processes over research agendas and priorities. Editorial boards of tropical medicine journals, dominated by scholars from high-income countries (HICs), risk reinforcing power imbalances and excluding context-driven expertise from endemic regions. This study examines the diversity of editorial boards across gender, geographic, socioeconomic, and geopolitical dimensions to assess systemic inequities. Method A systematic search of the National Library of Medicine (NLM) catalog was conducted via a targeted strategy between October and December 2024. After screening 153 journals for title relevance and applying exclusion criteria based on publication status, availability of editorial information, and global scope, 24 journals were selected. Data on 2,226 editorial board members were extracted from journal and institutional websites. Data on gender, country of affiliation (classified by World Bank income/regions), and geopolitical groups (G7, G20, BRICS) were extracted from public sources. Gender determination used a sequential approach (journal descriptions, Genderize.io, and consensus). Descriptive statistics were used to perform the analysis. Results The editorial board comprised 2,226 members, 66% male, 31.2% female, and 2.8% undetermined, from 120 nations. The regional contributions included Europe and Central Asia (21.9%), North America (20.9%), East Asia and the Pacific (16.6%), and Latin America and the Caribbean (16.2%), whereas Sub-Saharan Africa (11.2%), South Asia (9.7%), and the Middle East and North Africa (3.4%) were underrepresented. Over half (52.8%) were affiliated with high-income countries. Geopolitically, 40.3% were from the G7, 67.1% were from the G20, and 24.2% were from the BRICS. Some journals showed skewing, with 85.2% North American representation and 90.3% East Asia–Pacific dominance. Conclusion Tropical medicine editorial boards are steeped in systemic inequities that echo colonial legacies, with the overrepresentation of HICs and men limiting LMIC perspectives and local expertise. This imbalance undermines research relevance and ethical integrity by prioritizing Global North agendas over the needs of populations most affected by tropical diseases. To address these disparities, substantial reforms are essential. Strategies such as instituting DEI (Diversity, Equity and Inclusion), creating targeted mentorship programs for LMIC researchers, and enforcing transparent, bias-resistant recruitment practices are important. Such measures will create a more inclusive editorial landscape that aligns research priorities with global health needs, promoting equitable and contextually relevant solutions.